1999
DOI: 10.1096/fasebj.13.14.2071
|View full text |Cite
|
Sign up to set email alerts
|

T cell activation responses are differentially regulated during clinorotation and in spaceflight

Abstract: Studies of T lymphocyte activation with mitogenic lectins during spaceflight have shown a dramatic inhibition of activation as measured by DNA synthesis at 72 h, but the mechanism of this inhibition is unknown. We have investigated the progression of cellular events during the first 24 h of activation using both spaceflight microgravity culture and a ground-based model system that relies on the low shear culture environment of a rotating clinostat (clinorotation). Stimulation of human peripheral blood mononucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
83
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 47 publications
8
83
0
Order By: Relevance
“…Furthermore, CD3 surface expression reconstituted after T cell activation during 1g conditions but not in microgravity [27]. Investigations of TCR internalization in stimulated human PBMCs using rotating wall vessel system revealed that CD3 internalization was delayed in simulated microgravity [30] an effect in accordance with our findings of gravity-dependence of CD3 surface expression.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, CD3 surface expression reconstituted after T cell activation during 1g conditions but not in microgravity [27]. Investigations of TCR internalization in stimulated human PBMCs using rotating wall vessel system revealed that CD3 internalization was delayed in simulated microgravity [30] an effect in accordance with our findings of gravity-dependence of CD3 surface expression.…”
Section: Discussionsupporting
confidence: 82%
“…Under our chosen experimental conditions (60 rpm, 4 mm pipette diameter), a maximal residual acceleration of 2x10 -3 g was calculated at the outer radius of the pipette and decreases towards the center. 2D clinorotation with this experimental setup is an established model system for the simulation of microgravity using T lymphocytes and other cell types [13,30,31,32] A recent study (ESA Ground-based facilities / GBF project) compared different ground based microgravity platforms to real microgravity and identified fast 2D clinorotation as a good simulation of microgravity suitable for cell culture studies. In accordance to recommendations from the same study we will refer to clinorotation-induced microgravity as simulated microgravity [33].…”
Section: Methodsmentioning
confidence: 99%
“…And while the divergence of plants and animals largely prevents specific gene comparisons in spaceflight responses, certain classes of genes seem similarly affected by spaceflight. Calcium-mediated signal transduction is impacted by spaceflight in both plants and animals (Hughes-Fulford et al, 1998;Hashemi et al, 1999;Paul et al, 2001;Salmi and Roux, 2008), and genes affected by calcium signaling are differentially expressed. Heat shock proteins are highly conserved in both kingdoms, and heat shock genes are upregulated in some spaceflight studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations conducted in space laboratories and with instruments averaging the gravity vector, and thus simulating conditions of reduced gravity, have shown that isolated cells may change their behavior under altered gravitational conditions. Loss of cell activation [Cogoli et al, 1984], perturbation of signal transduction [Schmitt et al, 1996;Hashemi et al, 1999] and modification of genetic expression [Walther et al, 1998;Hammond et al, 1999] have been described. This suggests that some of the mechanisms at the roots of the systemic effects observed in weightlessness, such as depression of the immune system [Gmü nder and Cogoli, 1996] …”
mentioning
confidence: 99%